The Influence of Investment Motivation, Minimum Capital, Investment Risk and Investment Knowledge on Investment Interest in the Capital Market in Students of the Faculty of Economics, State University of Medan - khafi puddin; Agus Firmansyah; Azizul Kholis (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
The problem in this study is the investment interest of students in the capital market which basically students have a fairly high investment interest, but because of a risk and the perception that investment requires large capital so that some of the students discourage investment. This study aims to determine empirical evidence regarding the effect of investment motivation, minimum capital, investment risk, and investment knowledge on investment interest in the capital market. The population in this study were all students of the Faculty of Economics, State Universitas Negeri Medan. From the population, the data collected were 60 respondents who became the research sample with the provisions using the purposive sampling method. In this study, the instrument test was carried out through validity and reliability tests. The data analysis technique used in this study is the classical assumption test, multiple linear regression analysis and hypothesis testing, t test and F test using SPSS version 22 software. The results of this study indicate that simultaneously investment motivation, minimal capital, investment risk and investment knowledge have a significant effect on investment interest in the capital market. While partially investment motivation has a positive and significant effect on investment interest in the capital market, minimal capital has a positive and significant effect on investment interest in the capital market, investment risk has no effect on investment interest in the capital market, and investment knowledge has no effect on investment interest in the capital market.